Toluene vapor sensing characteristics of novel copper(II), indium(III), mono-lutetium(III) and tin(IV) phthalocyanines substituted with 2,6-dimethoxyphenoxy bioactive moieties - (:unkn) unknown (WORLD SCI PUBL CO INC, 2018)
This study presents the synthesis, characterization and toluene sensing properties of copper(II), indium(III) acetate, mono-lutetium(III) acetate and tin(IV) phthalocyanines substituted with 2,6-dimethoxyphenol bioactive groups at the peripheral and non-peripheral positions. The effects of the substituent's position on the toluene vapor detection capabilities of these compounds were investigated. Adsorption data were analyzed by using first-order and Elovich equations in order to investigate the adsorption kinetics. It was found that the kinetics of the toluene adsorption strongly depends on the position of the substituent groups. Our results showed that the Elovich equation fits the experimental data well for non-peripherally substituted Pc based sensors, while the pseudo first-order model best describes the adsorption data for peripheral substituted Pc based sensors.
Keywords: adsorption kinetics; Elovich model; 2,6-dimethoxyphenoxy; phthalocyanine; synthesis; toluene sensing; LANGMUIR-BLODGETT-FILMS; ZINC PHTHALOCYANINE; THIN-FILMS; PHOTODYNAMIC ACTIVITIES; ROOM-TEMPERATURE; NO2 DETECTION; GAS SENSOR; KINETICS; ADSORPTION; COMPLEXES